(untitled) (Comprehensive Journal of Science, 2026)
Precocious puberty in girls is an increasing public health concern, particularly in societies experiencing rapid nutritional transitions. Beyond genetic and endocrine factors, growing evidence suggests that dietary patterns may be associated with hormonal dysregulation and psychological disturbances. This descriptive review synthesizes observational literature examining the relationship between dietary habits and hormonal and psychological imbalances in girls with precocious puberty. Findings indicate that diets high in energy density, ultra-processed foods, added sugars, and animal fats are commonly linked to altered hormonal profiles and greater psychological vulnerability, whereas more balanced dietary patterns tend to be associated with relatively stable hormonal regulation and better psychosocial outcomes. Nevertheless, the evidence remains heterogeneous and context-dependent, underscoring the need for further well-designed observational studies, particularly in underrepresented settings.